The Effect of LEDs on Biomass and Phycobiliproteins Production in Thermotolerant Oscillatoria sp. (2022)
This study evaluates the role of different LED lights (white, blue/red), intensity (µmol m−2 s −1 ), and photoperiod in the production of biomass and phycocyanin-C, allophycocyanin and phycoerythrin (C-PC, APC, and PE respectively) from a novel thermotolerant strain of Oscillatoria sp. Results show that a mixture of white with blue/red LEDs can effectively double the biomass concentration up to 1.3 g/L, while the concentration of the selected phycobiliproteins increased proportionally to biomass. Results also indicate that high light intensities (>120 µmol m−2 s −1 ) can diminish the final concentration of C-PC, APC, and PE, significantly reducing the overall biomass produced. Finally, the photoperiod analysis showed that longer light exposure times (18:6 h) improved both biomass and phycobiliproteins concentration. These results demonstrate that the application of LEDs to produce a novel strain of Oscillatoria sp can double the biomass concentration, and the photoperiod regulation can eventually enhance the final concentration of specific phycobiliproteins such as APC and PE.